Abdominal ultrasound for surgeons - Hagopian, Ellen J.; Machi, Junji (New York : Springer, 2014)
Abdominal Ultrasound for Surgeons provides a comprehensive guide to the use of ultrasonography in surgical practice of abdominal diseases. The content is divided into three major sections, with the final section being dedicated to the logistics of incorporating ultrasound into a surgical practice. In Part I : The Basics, the principles of ultrasonography are reviewed focusing on ultrasound physics, equipment and instrumentation. A detailed approach to the various scanning methods with image and artifact interpretation is demonstrated with illustrations and images. In Part II : Anatomy, Application and Intervention, ultrasound anatomy and its use in surgery are detailed. The normal and abnormal ultrasound anatomy of specific abdominal organ or organ systems (esophagus, liver, pancreas, biliary, stomach, anorectum, vascularabdominal wall) with illustrations and images are demonstrated. A state-of-the-art review of the major applications of surgical abdominal ultrasound is provided in this section ranging from trauma ultrasound and laparoscopic staging to techniques in ultrasound guidance and three-dimensional targeting. In Part III : Ultrasound in Surgical Practice, the practical aspects of incorporation of ultrasound into a surgical practice are addressed with topics ranging from credentialing to coding and billing. Abdominal Ultrasound for Surgeons will serve as a very useful resource and guide for surgeons and students with little to some experience in ultrasound, including practicing surgeons, surgical fellows and surgical residents.
Keywords: ECOGRAFIA INTRAOPERATORIA; ABDOMEN -- DIAGNOSTICO POR IMAGENES; ABDOMEN -- CIRUGIA